Gentle Parenting in The Light of The Sunnah: Cultivating Gen Z Morality Toward a Maslahat Family - Hamid, Abdul; Qomaruddin, Muhammad; Siti Rosdianti (An-Nuha : Jurnal Kajian Islam, Pendidikan, Budaya dan Sosial, 2025)
Paradigms of child-rearing styles are constantly evolving in line with the times amid the moral crisis of Generation Z. This study aims to examine gentle parenting from the perspective of the Hadith as an effort to foster morality in Generation Z towards a beneficial family. The research method used is qualitative with a descriptive-analytical approach. The results of this study indicate that gentle parenting emerges as an ethical and spiritual response that shapes children's character holistically through consistent love, justice, the cultivation of manners and noble character, and the sharing of inspiring stories from the Prophets and Islamic figures that touch the emotional and affective dimensions of children. When grounded in the principles of mu'ādalah (justice), mubādalah (mutuality), and muwāzanah (balance), this parenting style not only produces morally upright children but also strengthens the family as an institution of well-being. Gentle parenting finds strong legitimacy through the hadiths of the Prophet Muhammad, which emphasize the importance of love, kindness, and setting a good example in raising children. This study recommends that the government, families, teachers, and journalists oversee contemporary Islamic-based parenting patterns in responding to the social complexities of the modern era.